THE BORROWED WORDS IN FIERSA BESARI’S CATATAN JUANG - Siti Rubaiyah; Hendra Husnussalam (IKIP Siliwangi, 2024)
The aim of this research is to find out how many and types of borrowed words that used in Fiersa Besari’s Catatan Juang. A novel tells about experiences of Juang, the main character. The author of this novel is known as an artist who has multi-talented starting from writer, youtuber, music composer, and singer. The method of this research is qualitative research and the object is English borrowed words in the novel entitled Catatan Juang by Fiersa Besari, bagian satu. Borrowed words can be classed into three types; loan words, loan blends and loan shifts. In loan words, language users is duplicating the item or idea from the source language. Loan blends is replicating native words to the similar meanings. Loan shifts is naming or defining one native element. Based on the analysis, the writer found 55(22,9%) loan words, 139(57,9%) loan blends, and 46(19,2%) loan shifts in sub bab of the novel. Based on the data the most dominant type that used in this novel is loand blends. The results of this study indicate that borrowed words not only can be acquired by the spoken language but also by written language.